ANALISIS KELAYAKAN BISNIS CATERING NUTRIPLATES DITINJAU DARI ASPEK TEKNIS - Salsabilla, Salma Nadia; Latifah , Luluk (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2024)
Feasibility analysis in a business is very important in running the business. There are several aspects in a business feasibility analysis, one of which is the technical aspect. The purpose of this research is to identify the business feasibility in one of the technical aspects that need to be considered, such as business location, layout and production capacity, technology and equipment, processing system, Human Resources (HR), and storage and distribution. This research uses a case study method with NutriPlates Catering, which is an UMKM in the catering field. The research results show that the technical aspects carried out by NutriPlates Catering include business location, human resources (HR), technology, equipment, processing, and distribution.